Actividad lúdica on-line, en el desenvolvimiento y autonomía para el fomento de la creatividad en los niños del nivel de educación inicial ii, en la Unidad Educativa Fiscomisional “San Carlos”, del cantón Quito, provincia de Pichincha, durante el período lectivo de 2021-2022. - Mejía Rueda, Josselinne Pamela (2022)
The new learning scenarios within virtual education have new methodologies, strategies and even teaching resources as support for students and teachers. The objective of this research is about the online playful activity, in the development and autonomy for the promotion of creativity, in addition, the field work was carried out in the boys and girls of the level of Initial Education II, in the Unit Educational Fiscal Mission "San Carlos", of the Quito canton, province of Pichincha, during the academic period from November 2021-2022. It was based on an exhaustive investigation and the data obtained was compiled through observation sheets to ratify that it is necessary to incorporate online playful activities and implement technological materials with the certainty of favoring the autonomous learning of infants